Isu Kekerasan Seksual di Lingkungan Kampus dalam Film Dear Nathan: Thank You Salma - Rina Nurfiana; Monika Pretty Aprilia (Unitri Press, 2023)
Cases of sexual violence against women in Indonesia continue to increase from various sectors, including education. Universities are places that have the highest percentage of cases when compared to other education sectors. Film is one of the media used to describe the culture and reality that is happening in today's society and is used as a medium of communication to convey messages to the public. The film Dear Nathan: Thank You Salma talks about the issue of sexual violence against women in the campus environment. In the film, the victim is described as a woman who is weak and powerless over the power possessed by the perpetrator and supported by a patriarchal culture and a culture of victim blaming. The researcher was used qualitative method as a research approach and uses a textual analysis research methodology by interpreting, exploring the finding, revealing the construction of ideology, and values that exist in a text with other texts. The object of this research is the depiction of the issue of sexual violence in the campus environment in the film Dear Nathan: Thank You Salma. The result of this research is the finding of sexual violence experienced by the victim and the resistance made by the victim ended in vain. Abstrak Kasus kekerasan seksual terhadap perempuan di Indonesia terus mengalami peningkatan dari berbagai sektor, tidak terkecuali di lingkungan pendidikan. Perguruan tinggi menjadi tempat yang memiliki persentase kasus yang paling tinggi jika dibandingkan dengan sektor pendidikan lainnya. Film menjadi salah satu media yang digunakan untuk menggambarkan budaya dan realitas di masyarakat saat ini dan dijadikan sebagai media komunikasi untuk menyampaikan berbagai pesan kepada khalayak. Film Dear Nathan: Thank You Salma menjadi salah satu film yang menceritakan tentang isu kekerasan seksual terhadap perempuan di lingkungan kampus. Dalam film tersebut korban digambarkan sebagai perempuan yang lemah dan tidak berdaya atas kuasa yang dimiliki pelaku serta didukung dengan adanya budaya patriarki dan budaya victim blaming. Peneliti menggunakan metode kualitatif sebagai pendekatan penelitian dan menggunakan metodologi penelitian analisis tekstual dengan cara memaknai, mengupas dan mengungkapkan konstruksi ideologi, nilai-nilai yang ada di dalam sebuah teks dengan teks lainnya. Objek dari penelitian ini adalah penggambaran isu kekerasan seksual di lingkungan kampus dalam film Dear Nathan: Thank You Salma. Hasil dari penelitian ini adalah ditemukannya adanya kekerasan seksual yang dialami korban dan perlawanan yang dilakukan korban berakhir sia-sia.